The Capacity Building of Smes in Semanu, Gunung Kidul Through Digital Marketing Socialization and Training - Syamsul Hadi; Sugiyamin Syamsul; Anselmus Sudirman; Lina Setiawati; Nur Rokhman; Nurul Myristica Indraswari (IMPACTS: International Journal of Empowerment and Community Services, 2023)
Purpose This community service aims to socialize and train appropriate Digital Marketing strategies for SMEs in Padukuhan Pragak, Semanu Gunung Kidul, to increase competition and adaptive capacity. Methods - Participatory Rural Appraisal (PRA) is used in community service to develop the community's potential. Result and discussions - Numerous potentials must be developed; this service process is divided into three stages: pre-implementation, implementation, and evaluation of the service program managed to carry out. Conclusion - Avoid being stuck in one's comfort zone by constantly innovating in products, distribution channels, various marketing networks, increasing knowledge, and being active in charitable contributions.